2016
DOI: 10.1108/ijmpb-10-2014-0067
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of team turnover intentions in temporary organizations

Abstract: Purpose – The purpose of this paper is to shed light on the antecedents of team turnover intentions in temporary organizations such as projects, programs, or temporary teams. Design/methodology/approach – The authors systematically combine the findings from the literature on the antecedents of turnover intentions in permanent organizations (PO) with the characteristics of temporary organizations (TO) and develop a research model comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 113 publications
1
23
0
Order By: Relevance
“…Despite the recent growth of research on TOs (Bakker, ), only little has been done to differentiate turnover intentions from temporary as opposed to permanent organizations. We define turnover intentions from temporary organizations as an employee's willingness to withdraw from a TO, regardless of whether the employee wants to quit the surrounding PO as well (Nuhn and Wald, ). Previous studies confirmed that turnover intentions from POs cause detrimental effects on employees' performance behavior (Hui et al, ).…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the recent growth of research on TOs (Bakker, ), only little has been done to differentiate turnover intentions from temporary as opposed to permanent organizations. We define turnover intentions from temporary organizations as an employee's willingness to withdraw from a TO, regardless of whether the employee wants to quit the surrounding PO as well (Nuhn and Wald, ). Previous studies confirmed that turnover intentions from POs cause detrimental effects on employees' performance behavior (Hui et al, ).…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
“…As employees develop turnover intentions from TOs, they will increasingly think about and search for alternative future positions to work in. Within TOs, future job placement also encompasses the appointment to other TOs within the same PO (Nuhn and Wald, ). In order to assess the availability of desirable alternatives, employees will increasingly show active job search and evaluation behavior (Sager et al, ; Blau, ).…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
See 3 more Smart Citations